2012
DOI: 10.1007/s10549-012-2376-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt, mTOR, and the estrogen receptor as a signature to predict tamoxifen treatment benefit

Abstract: The frequent alterations of the PI3K/Akt/mTOR-growth signaling pathway are proposed mechanisms for resistance to endocrine therapy in breast cancer, partly through regulation of estrogen receptor α (ER) activity. Reliable biomarkers for treatment prediction are required for improved individualized treatment. We performed a retrospective immunohistochemical analysis of primary tumors from 912 postmenopausal patients with node-negative breast cancer, randomized to either tamoxifen or no adjuvant treatment. Phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 42 publications
5
65
0
4
Order By: Relevance
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, a retrospective immunohistochemical study of primary tumors showed that overactivity of the AKT pathway was significantly associated with a reduced response to tamoxifen therapy (13). In another study, the overexpression of phosphorylated AKT or active AKT (pAKT) was detected in 58% of breast cancer samples, and survival analyses revealed that patients whose tumors were pAKTpositive were more prone to relapse with distant metastases (14).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging mechanism of endocrine resistance is the interaction between the PI3K-protein kinase B-mTOR and ER signaling pathways (22)(23)(24). In a previous study involving patients with newly diagnosed breast cancer, neoadjuvant everolimus combined with letrozole improved the clinical response rate and decreased tumor cell viability, compared with letrozole alone (42).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the phosphoinositide 3-kinase (PI3K)-protein kinase B-mammalian target of rapamycin (mTOR) and ER signaling pathways is an additional emerging mechanism of endocrine resistance (22)(23)(24). mTOR is a downstream target in the HER2 signaling pathway and is associated with the activity of the ER signaling pathway.…”
Section: Introductionmentioning
confidence: 99%